Stimulation of chemokines in human endometrial stromal cells by tumor necrosis factor-α and interferon-γ is similar under apoptotic and non-apoptotic conditions - Spratte, Julia; Schütz, Florian; Rom, Joachim; Fluhr, Herbert (Archives of gynecology and obstetrics, 2018)
Purpose: Tumor necrosis factor (TNF)-α and interferon (IFN)-γ are pro-inflammatory cytokines which have been shown to be involved in the pathophysiology of implantation disorders. Both cytokines in combination are able to sensitize primarily resistant human endometrial stromal cells (ESCs) to Fas-induced apoptosis. Since CCL (CC-chemokine ligand) 5 and CCL2 are important regulators of the endometrial immune cell population, we examined the impact of TNF-α and IFN-γ on these two chemokines under non-apoptotic and apoptotic conditions. Methods: ESCs were isolated from hysterectomy specimens, decidualized in vitro and incubated with TNF-α, IFN-γ, an activating anti-Fas antibody and a caspase-inhibitor. CCL5 and CCL2 were measured using ELISA and real-time RT-PCR. Apoptosis was determined by flow cytometry, and cellular viability and membrane integrity were measured by fluorescent assays. Results: The secretion of CCL5 and CCL2 was stimulated in undifferentiated and decidualized ESCs by the combination of TNF-α and IFN-γ under non-apoptotic as well as apoptotic (with Fas-stimulation in parallel) conditions. TNF-α or IFN-γ alone did not have this effect. The stimulatory influence of TNF-α plus IFN-γ on CCL5 and CCL2 in ESCs was also seen on the transcriptional level. Inhibition of cell death by a caspase-inhibitor had no influence on the secretion of CCL5 and CCL2 in ESCs under apoptotic stimulation. Conclusion: TNF-α and IFN-γ modulate the secretion of chemokines in ESCs independently of Fas-induced apoptosis. These results suggest a constant response pattern on pro-inflammatory cytokines within the population of human ESCs.